Functional Disorders of the Biliary Tract and Cholelithiasis: Analysis of a Possible Relationship - Yu. O. Shulpekova; I. R. Popova; V. M. Nechaev (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2024)
Aim: Diagnostic criteria for functional disorders of the biliary tract are presented in the materials of the Rome IV consensus, as well as expert councils of Russian and foreign specialists. Episodes of functional biliary pain are caused by a violation of bile outflow through the cystic duct and sphincter of Oddi. It has been suggested that there is a “biliary continuum” in which in some patients’ biliary dysfunction is transformed into cholelithiasis.   Key points. Lithogenic bile is considered as the pathophysiological basis for the development of biliary dyskinesia and cholelithiasis. Lithogenic bile provokes inflammation of low grades in the mucous membrane of the biliary tract, decreased contractility of the gallbladder and impaired relaxation of the biliary sphincters, impaired physiological response to cholecystokinin. Changes in motility of the biliary tract may be associated with the influence of hydrophobic bile salts and impaired eicosanoid metabolism. Hyperplasia of the epithelium and muscle layer, hypersecretion of mucin and cholesterol precipitation further impair the outflow of bile. Experimental data and some clinical observations indicate the possibility of transformation of biliary dysfunction into cholelithiasis. Dysfunction of the sphincter of Oddi is one of the possible consequences of cholecystectomy and, in fact, acts as a variant of postcholecystectomy syndrome. The basis for the treatment of biliary dysfunctions are antispasmodics of different classes, which can be combined with ursodeoxycholic acid. The biliary tract-selective antispasmodic hymecromone has shown high effectiveness in relieving biliary pain, which also has a moderate choleretic effect and the ability to prevent the crystallization of cholesterol in bile and can be used both for functional diseases and for cholelithiasis. The domestic drug hymecromone “Odecromone” entered the pharmaceutical market.   Conclusion. There is no doubt that the relevance of further study of the patterns of development of biliary dysfunctions and GI is obvious. The study of this problem will contribute to the development of effective preventive approaches, including in the field of nutraceuticals.